2017
DOI: 10.1093/hmg/ddx013
|View full text |Cite
|
Sign up to set email alerts
|

Relationships linking emotional, motor, cognitive and GABAergic dysfunctions in dystrophin-deficient mdx mice

Abstract: Alterations in the Duchenne muscular dystrophy (DMD) gene have been associated with enhanced stress reactivity in vertebrate species, suggesting a role for brain dystrophin in fear-related behavioral and cognitive processes. Because the loss of dystrophin (Dp427) reduces clustering of central γ-aminobutyric acid (GABAA) receptors, it is suspected that local inhibitory tuning and modulation of neuronal excitability are perturbed in a distributed brain circuit that normally controls such critical behavioral func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(101 citation statements)
references
References 89 publications
10
91
0
Order By: Relevance
“…In this present study male mdx mice were group houses (average 4 males per cage) and exposed to the same maze for 5 consecutive days, and yet a proportion of mdx mice still exhibit complete lasting tonic immobility (freezing response) at 12 months old during the Barnes maze test. This phenotype could be used to potentially assess the dynamics of therapeutic agents targeting brain dysfunctions in this model of DMD, as similarly suggested by Vaillend and Chaussenot [75] .…”
Section: Longitudinal Cognitive Profilingmentioning
confidence: 80%
See 1 more Smart Citation
“…In this present study male mdx mice were group houses (average 4 males per cage) and exposed to the same maze for 5 consecutive days, and yet a proportion of mdx mice still exhibit complete lasting tonic immobility (freezing response) at 12 months old during the Barnes maze test. This phenotype could be used to potentially assess the dynamics of therapeutic agents targeting brain dysfunctions in this model of DMD, as similarly suggested by Vaillend and Chaussenot [75] .…”
Section: Longitudinal Cognitive Profilingmentioning
confidence: 80%
“…Furthermore, previous reports detail a potent freezing response in male mdx mice, expressed as lasting tonic immobility, reminiscent of the natural defensive deathfeigning posture that animals exhibit when confronted by a predator or other threat, which is theorised to involve a brain circuit that includes the amygdala [75] . Authors suggest that if mdx mice were group housed rather than singly housed, and exposed to a familiar environment, this response could be reduced.…”
Section: Longitudinal Cognitive Profilingmentioning
confidence: 99%
“…), GABAergic dysfunction (Sekiguchi et al . ; Vaillend & Chaussenot, ) and cognitive deficits (Chaussenot et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Dystrophin is ordinarily expressed in neurons (Lidov, 1996). In the mdx mouse model of DMD, studies indicate reduced number of corticospinal neurons (Sbriccoli et al 1995), damage to motor pathways (Carretta et al 2001), loss of neuronal projections (Pinto et al 2008), GABAergic dysfunction (Sekiguchi et al 2009;Vaillend & Chaussenot, 2017) and cognitive deficits (Chaussenot et al 2015). It is unclear whether dystrophin deficiency affects the nervous system control of breathing.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike the manifestations of the disease in the skeletal and cardiac muscle the symptoms of the brain in DMD are not of a progressive nature. It has been demonstrated that the dystrophin‐deficient mdx mouse displays alterations in learning, behavior, fear response, and memory . Glial fibrillary acidic protein was upregulated in the mdx‐4cv brain in an unbiased proteomic investigation, which is of considerable interest as it is a well‐established indicator of brain damage further evidencing brain involvement in DMD .…”
Section: Resultsmentioning
confidence: 97%